Neural Interfaces and Brain-Computer Interaction: Recent Developments and Future Challenges - Deshmukh, Pooja (Journal of Advanced Research in Instrumentation and Control Engineering, 2025)
Neural interfaces and brain-computer interaction (BCI) technologies have advanced significantly in recent years, offering groundbreaking possibilities in neuroprosthetics, assistive communication, and cognitive enhancement. By enabling direct communication between the brain and external devices, BCI systems have opened new avenues for medical applications such as motor rehabilitation, epilepsy treatment, and neurodegenerative disease management. These technologies leverage various signal acquisition methods, including invasive approaches like intracortical electrode arrays and non-invasive techniques such as electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS). Additionally, advancements in artificial intelligence (AI) and machine learning have significantly improved signal decoding accuracy, enhancing the real-time responsiveness and adaptability of BCIs. Despite notable progress, several challenges remain in neural interface development. Signal instability, biocompatibility concerns, and the long-term durability of implantable BCIs pose significant barriers to widespread clinical adoption. Moreover, ethical considerations surrounding cognitive privacy, autonomy, and potential misuse of BCI technology require careful regulation and policy frameworks. Addressing these issues will be crucial for ensuring the safe and effective integration of BCIs in both medical and non-medical applications. This review explores recent developments in neural interface technologies, including innovations in hardware, signal processing algorithms, and neurofeedback systems. We also examine the role of hybrid BCIs that combine multiple sensing modalities to improve robustness and reliability. Finally, we discuss future directions, emphasizing the need for user-friendly, minimally invasive, and cost-effective neural interfaces that can be seamlessly integrated into daily life, ultimately paving the way for a more inclusive and accessible brain-computer communication paradigm.